Penggunaan Media Stick Box untuk Mengenalkan Angka pada Anak Usia 5-6 Tahun di Kecamatan Kapuas Barat - Maulidha Maulidha; Nopasintalia Nopasintalia (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The ability to recognize numerical symbols is a crucial aspect of cognitive development that should be stimulated from an early age. This study aims to describe the process of using the stick box learning media by a teacher in introducing numbers to children aged 5–6 years and to explore its impact on children's understanding of numbers. This research employed a qualitative approach with a narrative design, focusing on the personal experiences of a teacher as the main participant. Data were collected through observation, interviews, and documentation. Observations were conducted four times to examine the learning process and children's responses to the media, while interviews were conducted twice to explore the teacher's insights regarding children's numerical understanding before and after using the stick box. Supporting documents such as lesson plans and activity photos were also collected. Data analysis involved reduction, presentation, and verification stages to generate a systematic narrative of the learning process. The results indicate that the creative use of the stick box media significantly improved children's ability to recognize numbers in an enjoyable and interactive way. The children showed increased learning motivation and were able to identify numbers more easily without notable difficulties. In conclusion, the stick box media serves as an effective alternative tool in supporting early childhood cognitive development, particularly in introducing numbers.